Self‐Assembly of 2D Nanosheets into 1D Nanostructures for Sensing NO2. Issue 9 (14th July 2021) - Zha, Jiajia; Yuan, Zhen; Zhou, Zhan; Li, Yang; Zhao, Jiangqi; Zeng, Zhiyuan; Zhen, Liang; Tai, Huiling; Tan, Chaoliang; Zhang, Hua
Abstract : Ultrathin 2D nanosheets are one of the appealing building blocks for constructing self‐assembled nanostructures. Herein, a facile, fast, and general solvent‐mediated route for the high‐yield and large‐scale self‐assembly of ultrathin 2D nanosheets into 1D nanofibers and nanorings is reported. Solution‐dispersed graphene oxide (GO), MoS2, TiS2, and TaS2 nanofibers with lengths of several tens of micrometers and diameters of 20–50 nm are formed via the self‐assembly of their corresponding single‐layer nanosheets by simply vibrating their tetrahydrofuran suspensions under vortex for 1 min at room temperature. Interestingly, by simply changing the solvent from tetrahydrofuran to acetone, nanorings with diameters of 200–500 nm can be obtained via a similar process. As a proof‐of‐concept application, the reduced GO (rGO) nanofibers obtained by thermal reduction of the GO nanofibers are used as the channel material to fabricate electronic gas sensor, showing good sensitivity (with a detection limit of ≈75 ppb) and selectivity toward NO2 . The simple assembly strategy can be used to assemble other ultrathin 2D nanomaterials into 1D nanostructures for various promising applications. Abstract : A simple and universal strategy is developed for high‐yield and scalable self‐assembly of ultrathin 2D nanosheets, including graphene oxide (GO), MoS2, TiS2, and TaS2, into 1D nanofibers and nanorings. As a proof‐of‐concept application, the reduced GO nanofibers are used as channel material to fabricate the electronic gas sensing device for sensing NO2 with good sensitivity and selectivity.